Analisis Penerapan Jumlah Sampling Powder Dalam Pengendalian Kualitas Dengan Metode MIL – STD 105D (Studi kasus di PT Sriwijaya Alam Segar) - Imansa, Muhammad; Pratiwi, Irnanda; Suryani, Faizah (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2020)
Production process activities in a company are to pursue the profits they get, this is the concept of the company to achieve the target and get the expected profit of the company. To achieve all that, the company is doing more quality improvement in terms of production processes, products, and personnel. Defective products that go into packaging and production that have not yet reached the target become an inhibiting factor in improving quality. This study aims to analyze the application of the number of sampling using the MIL-STD 105D method for normal and strict examination types. Samples from each product were analyzed so that the results obtained, namely for variants of PMG (Fried Noodle Powder) in 1 box = 3500 pcs, special inspection level 3 (S3) table F code and the number of samples 20 pcs with AQL (Acceptable Quality Level) 10% with ac = 5, re = 6. PSAK (Chicken Kremes Success Powder) in 1 box = 2500 pcs, (S3) code E and the number of samples 13 pcs with AQL 10%, ac = 3 and re = 4. By using normal MIL inspection - STD 105D then disability can be accepted for PMG and PSAK variants. But for a strict MIL-STD 105D examination, several boxes were rejected, for PMG 2 boxes were rejected and PSAK 5 boxes were rejected.